Analisis Pemilihan Supplier Bahan Baku Roti dengan Metode ANP (Analytic Network Process) dan Rating Scale (Studi Kasus: Roti Gembong Kota Raja di Balikpapan) - Lusiana Agustin Sesa; Farida Djumiati Sitania; Dharma Widada (Jurnal Optimalisasi, 2021)
Roti Gembong Kota Raja is a company engaged in the culinary field with a contemporary concept. Roti Gembong Kota Raja has the term "gembong" because of its puffed texture. The raw materials for producing this bread are wheat flour, sugar, salt, yeast, eggs, milk, butter, water, and others. This study aims to select the appropriate raw material suppliers for producing the bread. Assessment of supplier performance is for wheat flour and sugar. The wheat flour suppliers are suppliers "A", "B", and "C", while the suppliers for the sugar are suppliers "X", "Y", and. "Z". Data were collected through interviews and questionnaires distributed to the HRD of Roti Gembong Kota Raja. The obtained data were processed using the Analytic Network Process (ANP) method and Rating Scale methods. The ANP method can be used in decision making to calculate the weight of the criteria and sub-criteria of suppliers, while the Rating Scale method can be used to get the right order or priority of suppliers for wheat flour and sugar. There had 5 selected criteria and 18 sub-criteria in the selection of raw material suppliers for wheat flour and sugar. The results of data analysis using the ANP method showed the criteria weight that has the highest limit value on the raw materials of wheat flour and sugar, namely customer satisfaction. The results of the calculation of the final total performance of the wheat flour supplier with the Rating Scale showed that supplier B has the highest final performance score of 3.48162 with the high-performance category. Meanwhile, the final total performance of the sugar supplier showed that supplier X has the highest final performance score of 3.55081 with the high-performance category.